Kaidah "Adharurotu Tubihul Madhurot" dan Penerapannya dalam Bidang Kedokteran - Fauzi, Amir (2011)
This study is aimed at investigating the principle of fiqh foundation " adharurotu tubihul mahkdhuraat "and applying to medical matters . The study examines the definition of adh-darar (the harmful),and its argumentation by reference Al-Qur'an and Al-hadist, and than the meaning of prohibition and meaning of hajah which included in adharor, and the finally the researcher applied this rule into contemporery problem concerning the medical metters. This study is based on the inductive approach in collecting relevant juristic opinion of early and contemporary scholars, including the views expressed in "al-fatawa al-mu'ashirah" (the contemporary legal opinions) and than analytical method were also applied in order to establishing the strongest view on the metterr concerned. And than conclution method by applying the element of inductive and analytical approach by showing Islamic laws which have related by " adharurah tubihul mahdhurat" rule. and which are included into medical harmful basically on analogy and Islamic scholar opinions. This legislative principles consulted in this study are Al-Qur'an, Al-sunah, Al-qawaid al-ushuliyah, and qawa'id al-fiqhiyah.